Over a million students use our free study notes to help them with their homework
y= 24x^2 - 2x^(-1/2) + 3 - 2x^-2
Derivative of 3x^2 is 3*(derivative of x^2) which is 3*(2x)=6x. Derivative of 5x is 5*(Derivative of x) which is 5*1=5 and derivative of (-1) is 0. Hence the answer is derivative of f(x) defined above is ...
To answer this question we must rearrange the equation to isolate y.Firstly, add 4 to each side, giving 2x=2y+4; Finally, divide both sides by 2 giving x=(2y+4)/2.
Our technique here will be the same used to solve the problem 5(x+3) = 60, but we must take care at each step to decide whether our inequality changes direction.Firstly, we expand the brackets to give 5x ...
←
434
435
436
437
438
→
Internet Safety
Payment Security
Cyber
Essentials